2020
DOI: 10.3892/mmr.2020.11618
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol protects against cerebral ischemia/reperfusion‑induced apoptosis and oxidative stress via the Sirt1/FoxO1 signaling pathway

Abstract: reperfusion is a critical therapeutic intervention used following acute ischemic stroke; however, it may cause cerebral ischemia/reperfusion injury (ciri) and aggravate brain damage. Piceatannol (Pic), a hydroxylated analog of resveratrol, has been reported to exhibit anti-inflammatory effects. However, the detailed molecular mechanisms and its effects on CIRI have not been sufficiently assessed, and, to the best of our knowledge, current methods of prevention of ciri are limited. The aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Resveratrol up-regulates the expression of nitric oxide synthase (eNOS) and enzyme activity in vascular endothelial cells by up-regulating the expression of SIRT1, and increases the NO production to mediate vasodilation of the blood vessel ( 1 , 29 ). Resveratrol can enhance the ability of autophagy by activating Sirt1/Foxo1 pathway, prevent oxidative stress and apoptosis induced by H 2 O 2 ( 30 , 31 ), and prevent apoptosis and oxidative stress induced by ischemia/reperfusion ( 32 ). Resveratrol also improved endothelial dysfunction in obese and diabetic mice through SIRT1/PPAR pathway, and improved glucose absorption in adipocytes with insulin resistance ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol up-regulates the expression of nitric oxide synthase (eNOS) and enzyme activity in vascular endothelial cells by up-regulating the expression of SIRT1, and increases the NO production to mediate vasodilation of the blood vessel ( 1 , 29 ). Resveratrol can enhance the ability of autophagy by activating Sirt1/Foxo1 pathway, prevent oxidative stress and apoptosis induced by H 2 O 2 ( 30 , 31 ), and prevent apoptosis and oxidative stress induced by ischemia/reperfusion ( 32 ). Resveratrol also improved endothelial dysfunction in obese and diabetic mice through SIRT1/PPAR pathway, and improved glucose absorption in adipocytes with insulin resistance ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, PC structure confers a higher capability to scavenge ROS by modulating other pathways as well [ 143 ]. The mechanisms of PC mitigation of ROS involve stimulation of antioxidant enzymes such as SOD and CAT activities [ 144 , 145 ]. Moreover, PC improves mitochondrial functions by increasing complex I activity and ATP content [ 144 ].…”
Section: Sirt Modulationmentioning
confidence: 99%
“…PC has been demonstrated to induce mitochondrial biogenesis through the increase of expression and protein levels of SIRT1 and PGC1α under gamma-irradiation [ 144 ]. On the other hand, apoptosis is reduced by PC increase of anti and pro-apoptotic proteins such as Bcl-2 and BAX, respectively [ 145 ]. However, PC exhibits great cytoprotection potential against oxidative stressors; it was observed that at a high concentration, PC promotes depolarization of mitochondrial membrane that leads to cell death.…”
Section: Sirt Modulationmentioning
confidence: 99%
“…The pathway is suppressed and cell will suffer from oxidative injury after an ischemic stroke ( Fig. 5 ) [ 78 , 80 - 82 ]. Furthermore, in carotid arteries with unstable plaques, miR-200c, a biomarker for inducing endothelial dysfunction, could negatively regulate SIRT1, de-acetylated FoxO1, and other stable biomarkers.…”
Section: Pathological Roles Of Foxo1 After Strokementioning
confidence: 99%
“…Piceatannol (Pic), a natural stilbene found primarily in seeds, wines and fruits, has been shown to promote antioxidant and neuroprotective effects via activation of SIRT1/FoxO1 pathway. Pic-treated mice showed improvement in neurological and cognitive function [ 80 ]. Magnolol, found in the bark of M. grandiflora, can also increase the expression of SIRT1, leading to the downregulation of Ac-FoxO1 and activation of the synthesis of antioxidants to protect against oxidative stress injury.…”
Section: Treatment and Intervention Measures For Foxo1 After Strokementioning
confidence: 99%